Risk factors associated with high-dose methotrexate induced toxicities in primary central nervous system lymphoma - Li, Wenshu; Zhang, Sitian; Wu, Ruoyun; Li, Ying; Wei, Shifeng; Fu, Lin; Sun, Xuefei; Liu, Yuanbo; Zhao, Zhigang; Mei, Shenghui (Frontiers in Pharmacology, 2025)
High-dose methotrexate (HDMTX) is the cornerstone of the treatment for primary central nervous system lymphoma (PCNSL). The prevention of drug-induced toxicities is critical. This study aims to identify key factors associated with HDMTX-induced toxicities (hematotoxicity, hepatotoxicity and nephrotoxicit) in 713 Chinese PCNSL patients undergoing 3021 HDMTX treatment courses. Demographic data, administration information, laboratory tests, area under the curve, co-medications, and 30 single nucleotide polymorphisms were collected to analyze the association of HDMTX-related toxicities using PLINK and SPSS. Higher ALB level, female, ABCB1 rs1045642, MTHFR rs1801131, and MTHFD1 rs2236225 were associated with lower risk of anemia, while the combination of furosemide, torasemide, bumetanide, and levetiracetam associating with higher risk. Co-use of torasemide had higher incidence of neutropenia. Higher level of ALB was correlated with less leukopenia; torasemide and rs2236225 were related to more leukopenia. Female, furosemide, rs1801133, ABCG2 rs2231142, ABCC2 rs717620 were related to more thrombocytopenia, while rs1045642 and high ALB were related to less. Rs1801131 and female were correlated with more hepatotoxicity, whereas furosemide was correlated with less. In nephrotoxicity, female and rs1801394 were correlated with less, MTHFR rs1801131 and rs1801133 were correlated with more. In conclusion, higher ALB levels had a lower risk of HDMTX toxicities; loop diuretics and levetiracetam generally accelerated the occurrence of toxicities. Rs1801133 GG, rs1128503 GG + AG, rs2231142 AA+ AC, rs717620 TT + GT were associated with increased risk of toxicity; rs1045642 TT and rs1801394 GG + AG were less likely to develop toxicity.